The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1046/j.1523-1755.2002.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Medial artery calcification in ESRD patients is associated with deposition of bone matrix proteins

Abstract: In patients with ESRD undergoing renal transplantation, vascular calcification of the medial layer of the inferior epigastric artery is common (44%), can be detected by spiral CT, and is associated with deposition of bone matrix proteins. This implies an active cell-mediated process, raising hope that directed intervention can arrest this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
286
2
11

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(327 citation statements)
references
References 30 publications
18
286
2
11
Order By: Relevance
“…In agreement with our findings, Moe et al have recently reported that, in patients with ESRD, positive immunostaining for OPN in the artery is stronger in diabetes than in non-diabetes [23]. Remarkably, the plasma OPN levels of two participants were above 1,000 ng/ml.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our findings, Moe et al have recently reported that, in patients with ESRD, positive immunostaining for OPN in the artery is stronger in diabetes than in non-diabetes [23]. Remarkably, the plasma OPN levels of two participants were above 1,000 ng/ml.…”
Section: Discussionsupporting
confidence: 93%
“…Several investigators have reported that the elevated expression of OPN in vasculature has a crucial role in atherosclerotic calcification [6,8,23,30]; however, the significance of whether the enhancement is inducible or preventive to the vascular calcification has not been fully revealed. In addition, recent studies have shown that, in vascular wall cells, the expression of OPN is accelerated by advanced glycation end-products [31] and mechanical stress [32].…”
Section: Discussionmentioning
confidence: 99%
“…Osteopontin levels were increased (25,26) and ␣ smooth muscle actin levels were decreased (25) in calcified medial layers of cutaneous blood vessels in patients with calcific uremic arteriolopathy. Furthermore, staining for osteopontin and other bone matrix molecules was strongly correlated with medial calcification in epigastric arteries of dialysis patients (27). These data support the concept that SMC undergo phenotypic conversion to osteogenic cell type in the presence of hyperphosphatemia in both animals and humans.…”
Section: Mechanistic Evidence For Hyperphosphatemiainduced Calcificationsupporting
confidence: 72%
“…Concomitant with mineralization, the cells undergo a phenotypic change characterized by loss of smooth muscle specific gene expression and upregulation of genes commonly associated with bone differentiation including osteocalcin, osteopontin and Runx2. Similar phenotypic changes have also been observed in vivo in human as well as animal models of vascular calcification (46,49,50). Elevated P-induced phenotypic transition and mineralization were shown to be dependent on a sodium-dependent phosphate cotransporter, Pit-1, on the basis of their ability to be inhibited by phosphonoformic acid (37) and Pit-1 specific small interfering RNA (Giachelli and Li, unpublished data).…”
Section: Roles Of Ca and P In Vascular Smooth Muscle Cell Mineralizationsupporting
confidence: 54%